Effect of integrated use of lime, blended fertilizer and compost on productivity, nutrient removal and economics of barley (Hordeum vulgare L.) on acid soils of high lands in West Showa Zone of Ethiopia - Woubshet Demissie; Selamyihun Kidanu; Cherukuri V Raghavaiah (International Journal of Life Sciences, 2017)
A field experiment was conducted during 2015 rainy season to investigate the effect of integrated nutrient and lime application on soil fertility and productivity of barley at Telecho, Wolmera district in the highlands of Western Ethiopia. The experiment comprised nine treatments namely (t1):control, (t2):compost at 5t ha-1, (t3):lime at 611kg ha-1 , (t4) :compost at 5t ha-1 + lime at 611kg ha-1, (t5): lime at 611kg ha-1 + DAP 150 kg ha-1 and urea 72 kg ha-1research recommendation (60 kg n ha-1and 69 kg p2o5 ha-1), (t6):site specific fertilizer recommendation (npsb at 150 kg ha-1, kcl at 100 kg ha-1, n at 33 kg ha-1), (t7): lime at 611kg ha-1 + npsb at 150 kg ha-1, kcl at 100 kg ha-1, n at 33 kg ha-1, (t8): lime at 611kg ha-1 + compost at 5t ha-1 + npsb at 150 kg ha-1, kcl at 100 kg ha-1, n at 33 kg ha-1, (t9): lime at 611kg ha-1 + 2.5 t ha-1 compost with 50 % of site specific fertilizer recommendation (npsb at 75 kg ha-1, kcl at 50 kg ha-1, n at 16 kg ha-1 ) laid out in a randomized complete block design with 3 replicates. Lime requirement was determined based on exchangeable acidity. Soil analysis revealed that lime application raised soil pH from 3.80 to the pH level ranging from 6.63 to 6.86. Yield and yield components of barley was significantly affected by the treatments. The highest and significant crop yield response was obtained with t8 (5385.6 kg ha-1). Likewise nutrient uptake (n, p, k, s) was significantly higher in plots treated with t8 compared to t1, t2, t3, t4, t6. However, in most cases the difference in yield and yield attributes, nutrient uptake, and soil parameters due to t1, t2, t3,t4, t6, were not discernible suggesting that all elements of soil health and fertility issues should be addressed together. The highest net return (30633 birr ha-1) with MRR (666.81) was obtained with t9. Thus, integrated use of lime at 611kg ha-1 + 2.5 t ha-1 compost together with 50 % of soil test based fertilizer recommendation (npsb at 75 kg ha-1, kcl at 50 kg ha-1, n at 16 kg ha-1) for barley is advocated in the study area and other locations with similar agro-ecologies to maximize barley grain productivity ha-1 and higher economic return.